The Influence of Murabahah and Ijarah Financing on the Development of Micro, Small, and Medium Enterprises - Fithrah Kamaliyah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Islamic microfinance institutions like BMT use Murabahah and Ijarah financing to support Indonesia's micro, small, and medium enterprises (MSMEs). Yet little empirical evidence exists on how these instruments work together to advance MSME growth. This study investigates how Murabahah and Ijarah financing affect MSME development among BMT Bisma clients in Cipondoh, Tangerang City, filling the gap in research on their combined effectiveness. This quantitative study collected primary data through questionnaires distributed to 30 customers who received Murabahah and Ijarah financing via convenience sampling. The indicators measured include the amount of financing, increase in sales turnover, production capacity, capital efficiency, asset accumulation, business scale expansion, and smoothness of raw material procurement. Data analysis was done by multiple linear regression with SPSS software version 24. The findings show that Murabahah and Ijarah financing has a positive and significant influence on the development of MSMEs. Murabahah financing has a regression coefficient of B = 0.489 (β = 0.366; p < 0.001), while Ijarah financing has a regression coefficient of B = 0.512 (β = 0.473; p < 0.001), indicating that Ijarah financing has a relatively greater influence on the development of MSMEs. The coefficient of determination value (Adjusted R²) of 0.724 indicates that 72.4% of the variation in MSME development can be explained by these two financing variables, while the remaining 27.6% is shaped by other factors beyond the study. These findings confirm that Islamic financing, particularly through Murabahah and Ijarah schemes is essential in supporting the development of MSMEs.